Ferric Iron Reduction in Extreme Acidophiles - Malik, Luise; Hedrich, Sabrina (Frontiers in Microbiology, 2022)
Biochemical processes are a key element of natural cycles occurring in the environment and enabling life on earth. With regard to microbially-catalyzed iron transformation, research predominantly has focused on iron oxidation in acidophiles, whereas iron reduction played a minor role. Microbial conversion of ferric to ferrous iron has however become more relevant in recent years. While there are several reviews on neutrophilic iron reducers, this article summarizes the research on extreme acidophilic iron reducers. After the first reports of dissimilatory iron reduction by acidophilic, chemolithoautotrophic Acidithiobacillus strains and heterotrophic Acidiphilium species, many other prokaryotes were shown to reduce iron as part of their metabolism. Still, little is known about the exact mechanisms of iron reduction in extreme acidophiles. Initially, hypotheses and postulations for the occurring mechanisms relied on observations of growth behavior or predictions based on the genome. By comparing genomes of well-studied neutrophilic with acidophilic iron reducers (e.g. Ferroglobus placidus and Sulfolobus spp.), it became clear that the electron transport for iron reduction proceeds differently in acidophiles. Moreover, transcriptomic investigations indicated an enzymatically-mediated process in Acidithiobacillus ferrooxidans using respiratory chain components of the iron oxidation in reverse. Depending on the strain of At. ferrooxidans, further mechanisms were postulated, e.g. indirect iron reduction by hydrogen sulfide, which may form by disproportionation of elemental sulfur. Alternative scenarios include Hip, a high potential iron-sulfur protein, and further cytochromes. Apart from the anaerobic iron reduction mechanisms, sulfur-oxidizing acidithiobacilli have been shown to mediate iron reduction at low pH (<1.3) under aerobic conditions. This presumably non-enzymatic process may be attributed to intermediates formed during sulfur/tetrathionate and/or hydrogen oxidation and has already been successfully applied for the reductive bioleaching of laterites. The aim of this review is to provide an up-to-date overview on ferric iron reduction by acidophiles. The importance of this process in anaerobic habitats will be demonstrated as well as its potential for application.